Pattern, Causes, and Management of Ocular Injuries at Rural Community Setting of Bangladesh - Abul Hasnat Golam Quddus, Mohammad Shamsal Islam (Pakistan Journal of Ophthalmology, 2018)
Purpose: Ocular injury is a major cause of low vision and the second most common cause of unilateral, partial or total loss of vision after cataract of all age groups. Studies on community ocular injuries are almost absent in Bangladesh. This study was undertaken to investigate the pattern, cause and management of ocular injuries in Bangladesh. Material and Methods: This study was carried out at Dr. Ahmadur Rahman research center, University of Chittagong, Bangladesh from August 2014 to December 2017. Two sets of data were collected: one from the hospital files and another from the community. The samples were 425 for hospital and 126 for the community respectively. Results: The vast majority of the injuries were Open Globe (91%) and the rest Close Globe (9%). The most common type of injury was Penetrating (81.4%), followed by Lime Burn (7%), and Ruptured Globe (6.4%) and others was 5%. The most abnormalities in the structure were found in Cornea (91%), Conjunctiva (59%) and Iris and Pupil (48%). Open Globe Injury was as high as 91% for hospital patients as against only 18% for the community patients. Similarly Close Globe Injury was 82% among community patients as against 9% of hospital patients. Conclusion: The nature of injuries found in hospital and community setting is different. A new fact about the ocular injury of community married women is husbands’ physical assault and women even can’t seek treatment for the restriction of movement imposed by their husbands and kin. Key words: Close Globe, Open Globe, Sharp Objects, Visual Acuity, Blunt Injury, Community, Bangladesh